Disaster memorials and monuments : history, context and practice from around the world - Brataas, Kjell (New York, NY : Routledge, 2025)
"Bringing together the historical and the contemporary, the political and the personal, Disaster Memorials and Monuments: History, Context and Practice from around the World presents a wide-ranging understanding and exploration on memorials and monuments built in the aftermath of accidents, natural disasters and acts of violence. Disaster management expert, Kjell Brataas gives provides a compassionate voice to difficult and complex situations as well as practical advice based on lessons learnt through academic research, site visits and personal experience. Brataas illustrates a wide range of monuments and memorial projects from all over the world and explains the process of their creation and the challenges that occur in memorialization processes. He further proposes strategies for dealing with trials and controversies in similar future developments. Features include: Personal interviews with key stakeholders in the field of memorization, psychology and victim support, who have first-hand experience with memorial projects. Insights, lessons learned and advice from scholars, professors, politicians, support group leaders, survivors, bereaved, community leaders and neighbors. Reporting on more than 80 memorials from around the world, including New Zealand, Halifax, Las Vegas, Newtown, Sahara, Chile, Japan and Seoul. Suggested reading, including books, reports and presentations on the topic. Disaster Memorials and Monuments: History, Context and Practice from around the World is important reading for all practicing professionals, for those who study and teach the importance and the process of developing memorials and monuments, and for everyone interested in crisis management and the aftermath of disasters"--
History -- Principles of memorials -- Place making : where architecture meets collective memory -- Typical monuments and memorials -- Timeline of memorials -- Other ways -- Their stories -- Conclusions.
Keywords: Memorialization; Memorials; Monuments; Disasters -- History; Disaster victims -- Psychology; Collective memory; POLITICAL SCIENCE / General; SOCIAL SCIENCE / Disasters & Disaster Relief